2018
DOI: 10.1177/1755088218814072
|View full text |Cite
|
Sign up to set email alerts
|

Sovereign myths in international relations: Sovereignty as equality and the reproduction of Eurocentric blindness

Abstract: The concept of sovereignty still generates a considerable amount of debate in the discipline of International Relations. Using myth as a heuristic device, I argue that part of this confusion results from a mythical understanding of ‘sovereignty as equality’. Following the myth, sovereignty is seen as playing an equalising role in international relations, while international inequalities are depicted as existing despite the norm of sovereignty (and not as a result of it). The myth of sovereignty as equality thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Furthermore, the concept has perpetuated a myth of equality between 'sovereign' entities when political relations between these entities are clearly uneven and asymmetrical (Mathieu 2020). Applying the term sovereignty to Indigenous calls for self-determination is thus deceiving since the term implies equality while -as the UN Declaration on the Rights of Indigenous Peoples clearly outlines -the Westphalian sovereign state remains superior to selfgoverning Indigenous Peoples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the concept has perpetuated a myth of equality between 'sovereign' entities when political relations between these entities are clearly uneven and asymmetrical (Mathieu 2020). Applying the term sovereignty to Indigenous calls for self-determination is thus deceiving since the term implies equality while -as the UN Declaration on the Rights of Indigenous Peoples clearly outlines -the Westphalian sovereign state remains superior to selfgoverning Indigenous Peoples.…”
Section: Discussionmentioning
confidence: 99%
“…Protodiplomacy is paradiplomacy carried out to promote political identity, gain international recognition from other actors to become a sovereign state, and forward a separatist agenda within a country (Mathieu, 2020;Paquin, 2018). In his research, Mathieu (2020) showed that paradiplomacy and protodiplomacy are techniques that can simultaneously advance Canada and the provinces bilaterally and regionally.…”
Section: T Er At U R E R Ev I Ewmentioning
confidence: 99%
“…Protodiplomacy is paradiplomacy carried out to promote political identity, gain international recognition from other actors to become a sovereign state, and forward a separatist agenda within a country (Mathieu, 2020;Paquin, 2018). In his research, Mathieu (2020) showed that paradiplomacy and protodiplomacy are techniques that can simultaneously advance Canada and the provinces bilaterally and regionally. Schiavon (2019) carried out a comprehensive comparative study of the paradiplomacy of 11 federal systems in the world by explaining why and how substate actors conduct international relations and how the patterns of relations between federal authorities and local governments coordinate in the implementation of national foreign policy.…”
Section: T Er At U R E R Ev I Ewmentioning
confidence: 99%
“…The measures through which states are conventionally understood as establishing (or performing) sovereignty internally – towards their own polities – and externally – towards other states – were shaped by the needs and interests of the states negotiating the Treaty of Westphalia at the time (see, for example, Agnew, 2005; Glanville, 2011; Walters, 2002). Westphalian sovereignty emerged in modern Europe and is centred around a particular Eurocentric form of (inter)statehood (Mathieu, 2020). A territorialized understanding of sovereignty has since survived as the conventional, de jure understanding of sovereignty (Agnew, 2005).…”
Section: Questioning (External) Sovereignty Between States: a Postcol...mentioning
confidence: 99%
“…The current regulation of migration – including the right to exclude and/or deport – rests on historically long-established economic and political inequalities between states, including those related to rights of mobility and the customary international law regarding the exclusion of non-citizens. Mathieu (2020: 340) calls this mismatch a misleading ‘myth’, ‘providing an equal, unbiased and culturally neutral access to the same status to all the states which fulfil some supposedly universal standards’. Similarly, Bonilla (2017: 331) sees the major problem of the concept in the fact that it is used as an analytical category rather than interrogated as ‘a norm .…”
Section: Questioning (External) Sovereignty Between States: a Postcol...mentioning
confidence: 99%